Composite anti-seepage coating as well as preparation method and application thereof

By preparing a composite anti-seepage coating of redispersible graphene oxide-nano titanium dioxide composite powder and film-forming resin, the problem of anti-seepage of graphene coatings in crude oil storage tanks was solved, and effective barrier and protection against corrosive media was achieved.

CN119264786AActive Publication Date: 2025-01-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310820109.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2025-01-07
Estimated Expiration
2043-07-05

AI Technical Summary

Technical Problem

Existing graphene-based coatings are insufficient to meet the seepage prevention requirements of the complex and corrosive environment inside crude oil storage tanks, and graphene oxide has structural defects and is prone to agglomeration.

Method used

By reacting graphene oxide with a silane coupling agent in the presence of a solvent and reacting it with a titanium dioxide solution under acidic conditions, and by using polyaniline oligomers as a dispersant, a redispersible graphene oxide-nano titanium dioxide composite powder was prepared. This powder was then mixed with a film-forming resin to form a composite anti-seepage coating.

Benefits of technology

It achieves uniform dispersion of graphene oxide and improves the coating's resistance to oily media corrosion, providing a good barrier against corrosive media such as crude oil and tank bottom sediment water, thus solving the problem of traditional anti-seepage coatings protecting the inside of oil storage tanks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264786A_ABST
    Figure CN119264786A_ABST
Patent Text Reader

Abstract

The invention relates to the field of oil storage tank anti-seepage coatings, and discloses a composite anti-seepage coating and a preparation method and application thereof.The preparation method of the composite anti-seepage coating comprises the steps that 1, graphene oxide and a silane coupling agent are subjected to a contact reaction in the presence of a solvent, and drying is conducted to obtain a solid product; 2) carrying out contact reaction on the solution containing the solid product and a titanium dioxide solution under an acidic condition, and drying a contact reaction product to obtain the solid product; (3) dispersing and drying the second solid product obtained in the step (2) by using a polyaniline oligomer to obtain redispersible composite powder; and 4) mixing the obtained redispersible composite powder with film-forming resin. According to the invention, the novel titanium dioxide modified graphene oxide composite anti-seepage coating can be provided, so that the coating has a better oil medium corrosion resistance effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of anti-seepage coatings for oil storage tanks, and in particular to a titanium dioxide-modified graphene oxide composite anti-seepage coating and a preparation method and application thereof. Background Art

[0002] With the increase in crude oil import, export and transshipment, more and more vertical storage tanks are put into use. However, these oil products inevitably contain corrosive media such as chlorides, sulfates, and anaerobic bacteria, which often cause perforation of the inner wall of the tank and oil leakage. However, as the service time increases, storage tanks often cause soil and groundwater pollution due to corrosion and leakage. Therefore, how to effectively and long-term protect crude oil storage tanks to prevent medium penetration from having a negative impact on the storage tanks is an urgent problem that researchers need to solve.

[0003] Nowadays, surface coating protection technology is one of the most commonly used anti-seepage measures for storage tanks. This method has a simple process, wide applicability, low cost, and easy maintenance. It can directly block the penetration and diffusion path of corrosive media. However, due to the continuous deterioration of the quality of crude oil, the existing traditional anti-seepage coatings have been difficult to meet the safety requirements of actual oil storage, transportation, and production. As a derivative of graphene, two-dimensional sheet-structured graphene oxide has similar physical and chemical properties to graphene, and also exhibits higher mechanical strength and matrix dispersion properties than graphene. Therefore, graphene oxide plays an important role in improving the barrier properties of anti-seepage coatings. However, graphene oxide also has a large specific surface area and strong van der Waals force, which still cannot achieve a satisfactory dispersion effect. In addition, a variety of oxygen-containing functional groups are grafted on the surface of graphene oxide, which may cause nanostructure defects, and the density is slightly lower than that of graphene barrier materials. To this end, the coupling modification of graphene oxide using nano-titanium dioxide particles can enhance the dispersibility of graphene oxide on the one hand, and on the other hand, it can make up for the nanostructure defects of graphene oxide by blocking micropores, becoming a practical means of optimizing and modifying graphene oxide. CN105802452A discloses a method for preparing a graphene insulating coating, which is an anti-corrosion coating synthesized by dispersing graphene in a resin. CN106010091A discloses an anti-corrosion and anti-static coating and a preparation method thereof, which mainly disperses graphene and carbon nanotubes into epoxy resin through a dispersant to prepare an anti-static anti-corrosion coating. CN114958151A discloses a composite anti-corrosion material containing modified graphene oxide and a preparation method thereof, which improves the coating's ability to resist acidic and alkaline media. The graphene coatings prepared in the above three schemes are mainly used in external anti-corrosion fields such as marine chemicals and electrical equipment, and are not suitable for crude oil storage tanks. Summary of the invention

[0004] The purpose of the present invention is to overcome the drawbacks of existing graphene coating technology that it cannot meet the anti-seepage requirements of the complex corrosive environment inside crude oil storage tanks, while solving the structural defects and easy agglomeration problems of graphene oxide, and to provide a new titanium dioxide modified graphene oxide composite anti-seepage coating, so that the coating has better resistance to oil medium corrosion.

[0005] The modified graphene oxide preparation method of the present invention has the advantages of simple process and controllable process, and can make the graphene oxide filler better combined with the coating resin matrix to achieve uniform dispersion of graphene oxide. The new titanium dioxide modified graphene oxide composite anti-seepage coating provided by the present invention can produce a good barrier effect on corrosive media such as crude oil and tank bottom sediment water, solves the problem that traditional anti-seepage coatings are difficult to meet the internal protection of oil storage tanks, and is conducive to the application and development of graphene-based high-performance anti-seepage coatings.

[0006] In order to achieve the above object, the present invention provides a method for preparing a composite anti-seepage coating, wherein the method comprises:

[0007] 1) in the presence of a solvent, allowing graphene oxide and a silane coupling agent to undergo a first contact reaction, and subjecting the first contact reaction product to a first drying to obtain a first solid product;

[0008] 2) Under acidic conditions, subjecting the solution containing the first solid product to a second contact reaction with a titanium dioxide solution, and subjecting the second contact reaction product to a second drying to obtain a second solid product;

[0009] 3) using polyaniline oligomer as a dispersant to disperse the second solid product obtained in step 2), and thirdly drying to obtain a redispersible graphene oxide-nano-titanium dioxide composite powder;

[0010] 4) mixing the redispersible graphene oxide-nano titanium dioxide composite powder obtained in step 3) with a film-forming resin.

[0011] The weight ratio of the graphene oxide to the solvent in step 1) is 1:8-20, preferably 1:10-15.

[0012] Preferably, the weight ratio of the graphene oxide to the silane coupling agent is 1:3-18, preferably 1:5-15.

[0013] The first contact reaction is carried out under an inert atmosphere.

[0014] Preferably, the first contact reaction conditions include: temperature of 10-35°C, and reaction time of 0.2-2h.

[0015] Preferably, the first contact reaction conditions include: temperature of 25-30°C, 0.5-1h,

[0016] Preferably, the first drying conditions include: temperature of 70-150°C, time of 4-15h,

[0017] Preferably, the first drying conditions are: temperature of 90-110° C. and time of 6-10 h.

[0018] Wherein, in step 1), the solvent is selected from one or more of N'N-dimethylformamide, N'N-dimethylacetamide and N'N-dimethylpropionamide, preferably N'N-dimethylformamide,

[0019] Preferably, the silane coupling agent includes one or more selected from 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, preferably 3-aminopropyltriethoxysilane.

[0020] Wherein, the method further comprises: before the first drying, performing a first drying and washing step on the first contact reaction product.

[0021] In step 2), the solvent used in the solution containing the first solid product is selected from one or more of N'N-dimethylformamide, N'N-dimethylacetamide and N'N-dimethylpropionamide,

[0022] Preferably, the content of the first solid product in the solution containing the first solid product is 5-10% by weight.

[0023] Preferably, the acidic condition is a pH value between 3.5-5.5, preferably a pH value of 4-5;

[0024] Preferably, the acidic conditions are adjusted by adding acetic acid.

[0025] In step 2), the concentration of the nano titanium dioxide solution is 0.5-7% by weight, preferably 2-5% by weight.

[0026] Preferably, the weight ratio of the nano titanium dioxide to the graphene oxide is 1:1-4, preferably 1:1.5-2.5.

[0027] In step 2), the second contact reaction conditions include: temperature of 60-90°C, time of 5-12h,

[0028] Preferably, the second contact reaction conditions include: temperature of 80°C, time of 6-10h,

[0029] Preferably, the second drying conditions include: temperature of 45-100°C, time of 18-64h,

[0030] Preferably, the second drying conditions include: temperature of 50-90°C and time of 24-48h.

[0031] The method further comprises: before the second drying, performing a second drying and washing step on the second contact reaction product.

[0032] Preferably, the weight ratio of the graphene oxide to the polyaniline oligomer is 1:20-60, preferably 1:30-40.

[0033] In step 3), the average molecular weight of the polyaniline oligomer is 6000-10000, preferably 7000-8000,

[0034] Wherein, in step 3), the dispersion is ultrasonic dispersion,

[0035] Preferably, the ultrasonic dispersion conditions include: ultrasonic power of 100-500W, ultrasonic time of 0.2-5h,

[0036] Preferably, the conditions for ultrasonic dispersion include: ultrasonic power of 200-400W, and ultrasonic time of 0.5-3h.

[0037] In step 3), the third drying conditions include: temperature of 50-95°C, time of 6-30h,

[0038] Preferably, the third drying conditions include: temperature of 70-90° C. and time of 10-20 h.

[0039] In step 4), the redispersible graphene oxide-nano titanium dioxide composite powder obtained in step 3) and a part of the film-forming resin are ground and then mixed with another part of the film-forming resin.

[0040] Preferably, the redispersible graphene oxide-nano titanium dioxide composite powder and 5-20 weight % of the total amount of the film-forming resin are ground.

[0041] Preferably, the redispersible graphene oxide-nano titanium dioxide composite powder is ground with 10-15 weight % of the total amount of the film-forming resin.

[0042] Preferably, based on the composite anti-seepage coating, the content of the redispersed graphene oxide-nano-titanium dioxide composite powder is 0.1-5% by weight, preferably 0.2-3% by weight.

[0043] In step 4), the step of adding an auxiliary agent,

[0044] Preferably, the auxiliary agent is a pigment,

[0045] Preferably, based on the composite anti-seepage coating, the content of the auxiliary agent is 0.5-2% by weight.

[0046] In step 4), the film-forming resin is selected from one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, novolac epoxy resin, polyurea resin, polyurethane resin, silicone resin and fluorocarbon resin, preferably novolac epoxy resin.

[0047] According to a second aspect of the present invention, a composite anti-seepage coating prepared by the preparation method of the composite anti-seepage coating of the present invention is provided.

[0048] According to the third aspect of the present invention, the composite anti-seepage coating prepared by the method for preparing the composite anti-seepage coating of the present invention is used in the internal anti-seepage of oil storage.

[0049] The preparation method of the composite anti-seepage coating of the present invention obtains a composite anti-seepage coating, which has the advantages of simple process and controllable process, can produce a good barrier effect on corrosive media such as crude oil and water deposited on the bottom of the tank, solves the problem that traditional anti-seepage coatings are difficult to meet the internal protection of oil storage tanks, and is conducive to the application and development of graphene-based high-performance anti-seepage coatings. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 It shows the water vapor transmission rate of the barrier material of Test Example 1.

[0051] Figure 2 The figure shows the surface morphology of the anti-seepage material of Test Example 3 after being immersed in crude oil for 30 days.

[0052] Figure 3 It shows the relationship between the hardness of the anti-seepage material of Test Example 4 and the immersion time. DETAILED DESCRIPTION

[0053] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0054] According to a first aspect of the present invention, a method for preparing a composite anti-seepage coating is provided, wherein the method comprises:

[0055] 1) in the presence of a solvent, allowing graphene oxide and a silane coupling agent to undergo a first contact reaction, and subjecting the first contact reaction product to a first drying to obtain a first solid product;

[0056] 2) Under acidic conditions, subjecting the solution containing the first solid product to a second contact reaction with a titanium dioxide solution, and subjecting the second contact reaction product to a second drying to obtain a second solid product;

[0057] 3) using polyaniline oligomer as a dispersant to disperse the second solid product obtained in step 2), and thirdly drying to obtain a redispersible graphene oxide-nano-titanium dioxide composite powder;

[0058] 4) mixing the redispersible graphene oxide-nano titanium dioxide composite powder obtained in step 3) with a film-forming resin.

[0059] According to the present invention, the amount of the solvent can be selected according to the amount of the graphene oxide. In order to improve the dispersion performance of the graphene oxide in the organic solvent, preferably, the weight ratio of the graphene oxide to the solvent in step 1) is 1:8-20; more preferably, the weight ratio of the graphene oxide to the solvent in step 1) is 1:10-15.

[0060] According to the present invention, the amount of the silane coupling agent can be selected according to the amount of the graphene oxide. In order to increase the interlayer spacing of the graphene oxide, preferably, the weight ratio of the graphene oxide to the silane coupling agent is 1:3-18; more preferably, the weight ratio of the graphene oxide to the silane coupling agent is 1:5-15.

[0061] According to the present invention, preferably, in step 1), the first contact reaction is carried out under an inert atmosphere. The inert atmosphere can be implemented by introducing an inert gas, and as the inert gas, for example, nitrogen, argon, etc. can be mentioned. In a specific embodiment of the present invention, the inert gas can be introduced into the reaction system for bubbling. According to the present invention, preferably, the first contact reaction conditions include: a temperature of 10-35°C and a reaction time of 0.2-2h; more preferably, the first contact reaction conditions include: a temperature of 25-30°C and a reaction time of 0.5-1h.

[0062] According to the present invention, preferably, the first drying condition includes: temperature of 70-150° C., time of 4-15 h; more preferably, the first drying condition includes: temperature of 90-110° C., time of 6-10 h.

[0063] According to the present invention, in order to make the graphene oxide evenly dispersed, as the solvent contained in the first contact reaction, preferably, the solvent is selected from one or more of N'N-dimethylformamide, N'N-dimethylacetamide and N'N-dimethylpropionamide; more preferably, the solvent is N'N-dimethylformamide.

[0064] In the present invention, in order to make the graphene oxide uniformly dispersed, ultrasonic dispersion is performed in the solvent, and the ultrasonic dispersion conditions can be existing conditions that can be used for dispersion. Specifically, the ultrasonic dispersion conditions can include: ultrasonic power of 200-500W, ultrasonic temperature of 20-35°C, and ultrasonic time of 0.5-4h.

[0065] According to the present invention, from the perspective of the dispersibility of the composite filler in the anti-seepage coating, preferably, the particle size of the graphene oxide is 20-50 μm; more preferably, the particle size of the graphene oxide is 30-40 μm. The graphene oxide can be obtained by the Hummers method and / or a commercially available graphene oxide product.

[0066] According to the present invention, in order to graft-modify nano-titanium dioxide on the surface of graphene oxide, the first contact reaction contains a silane coupling agent. Preferably, the silane coupling agent is selected from one or more of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane; more preferably, the silane coupling agent is 3-aminopropyltriethoxysilane.

[0067] In the present invention, in order to remove the excess silane coupling agent and other impurities in the first contact reaction product, the method further includes the step of first drying and washing the first contact reaction product before the first drying. Preferably, the conditions for the first drying include: a temperature of 80-120°C and a time of 6-15h; more preferably, the conditions for the first drying include: a temperature of 100°C and a time of 8-10h.

[0068] According to the present invention, as a washing solution for washing the first contact reaction product and removing excess silane coupling agent and other impurities in the first contact reaction product, preferably, the washing solution is selected from one or more of ethanol, ethyl acetate, and tetrahydrofuran; more preferably, the washing solution is anhydrous ethanol. The washing times can be one or more times, preferably 3-5 times.

[0069] According to the present invention, in step 2), in order to achieve modification of graphene oxide by titanium dioxide, the solution containing the first solid product is obtained by mixing the first solid product with a solvent. The solvent used in the solution containing the first solid product is selected from one or more of N'N-dimethylformamide, N'N-dimethylacetamide and N'N-dimethylpropionamide; more preferably, the solvent used in the solution containing the first solid product is N'N-dimethylformamide.

[0070] In addition, the concentration of the solution containing the first solid product may be 3-17 wt %; preferably, the concentration of the solution containing the first solid product is 5-10 wt %.

[0071] According to the present invention, in order to ensure that the second contact reaction is fully carried out, in step 2), the system is adjusted to an acidic environment. Preferably, the acidic system can be adjusted by adding acetic acid and / or citric acid; more preferably, the acidic system can be adjusted by adding acetic acid. According to the present invention, preferably, the pH value is adjusted between 3.5-5.5; more preferably, the pH value is adjusted between 4-5.

[0072] According to the present invention, in order to produce a good barrier effect on corrosive media and solve the problem that traditional anti-seepage coatings are difficult to meet the internal protection of oil storage tanks, in a second contact reaction, a solution containing the first solid product is subjected to a second contact reaction with titanium dioxide.

[0073] According to the present invention, in step 2), the titanium dioxide is preferably used in the form of a solution, for example, it can be obtained by slowly centrifuging nano-titanium dioxide in deionized water and removing large particles in the supernatant. Preferably, the concentration of the nano-titanium dioxide solution is 0.5-7% by weight; more preferably, the concentration of the nano-titanium dioxide solution is 2-5% by weight.

[0074] According to the present invention, preferably, the weight ratio of the nano-titanium dioxide to the graphene oxide is 1:1-4; more preferably, the weight ratio of the nano-titanium dioxide to the graphene oxide is 1:1.5-2.5.

[0075] According to the present invention, preferably, the second contact reaction conditions include: temperature of 60-90°C, time of 5-12h; more preferably, the second contact reaction conditions include: temperature of 80°C, time of 6-10h.

[0076] According to the present invention, preferably, the second drying condition includes: temperature of 45-100°C, time of 18-64h; more preferably, the second drying condition includes: temperature of 50-90°C, time of 24-48h.

[0077] In the present invention, in order to remove the excess N'N-dimethylformamide in the second contact reaction product, the method further includes the steps of performing a second drying and washing on the second contact reaction product before performing the second drying. Preferably, the conditions for the second drying include: a temperature of 80-100°C and a time of 6-15h; more preferably, the conditions for the second drying include: a temperature of 90°C and a time of 8-10h.

[0078] The washing solution comprises one or more of ethanol, ethyl acetate and tetrahydrofuran, preferably anhydrous ethanol. The washing times can be one or more times, preferably 3-5 times.

[0079] According to the present invention, in order to improve the structural defects of graphene oxide and the dispersion performance of the material, polyaniline oligomer is used as a dispersant, and the second solid product is dispersed and dried for the third time.

[0080] According to the present invention, preferably, the average molecular weight of the polyaniline oligomer is 6000-10000; more preferably, the average molecular weight of the polyaniline oligomer is 7000-8000.

[0081] According to the present invention, preferably, the weight ratio of the graphene oxide to the polyaniline oligomer is 1:20-60; more preferably, the weight ratio of the graphene oxide to the polyaniline oligomer is 1:30-40.

[0082] According to the present invention, the dispersion method can be selected as ultrasonic dispersion. Preferably, the conditions of the ultrasonic dispersion include: ultrasonic power of 100-500W, ultrasonic temperature of 20-35°C, and ultrasonic time of 0.5-5h; more preferably, the conditions of the ultrasonic dispersion include: ultrasonic power of 200-400W, ultrasonic temperature of 25-30°C, and ultrasonic time of 1-3h.

[0083] According to the present invention, the ultrasonic dispersion can be performed once or multiple times. When multiple ultrasonic dispersions are performed, preferably after the previous ultrasonic dispersion, the dispersion is allowed to stand and solid-liquid separated to obtain a dispersion, and then the dispersion is subjected to acoustic ultrasonic separation. The standing conditions can be the conditions commonly used in the art, such as a standing temperature of 10-35°C and a standing time of 0.5-3h. The solid-liquid separation can be performed using various means of solid-liquid separation commonly used in the art, such as a rotation speed of 10000-13000r / min, a temperature of 25°C, and a time of 1.5-2h.

[0084] According to the present invention, the third drying conditions include: temperature of 50-95°C, time of 6-30h; more preferably, the third drying conditions include: temperature of 70-90°C, time of 10-20h.

[0085] According to the present invention, in order to further improve the anti-corrosion performance, preferably, the total amount of the redispersible graphene oxide-nano-titania composite powder is such that the total content of the redispersible graphene oxide-nano-titania composite powder in the composite anti-seepage coating is 0.1-5% by weight, and more preferably, the total amount of the redispersible graphene oxide-nano-titania composite powder is such that the total content of the redispersible graphene oxide-nano-titania composite powder in the composite anti-seepage coating is 0.2-3% by weight.

[0086] According to the present invention, in order to make the redispersible graphene oxide-nano-titanium dioxide composite powder more evenly dispersed, the redispersible graphene oxide-nano-titanium dioxide composite powder is ground with a portion of the film-forming resin, and the grinding can be carried out under the conditions commonly used in the art, for example, the grinding temperature can be 10-25°C, and the grinding time can be 0.5-2h, preferably 1-1.5h.

[0087] According to the present invention, preferably, 5-20 weight % of the total amount of the redispersible graphene oxide-nano-titania composite powder and the film-forming resin are ground; more preferably, 10-15 weight % of the total amount of the redispersible graphene oxide-nano-titania composite powder and the film-forming resin are ground.

[0088] In the present invention, after the grinding, it is mixed with another part of the film-forming resin. Preferably, the conditions for mixing with another part of the film-forming resin include: temperature of 10-30°C, time of 20-80min; more preferably, the conditions for mixing with another part of the film-forming resin include: temperature of 20-25°C, time of 30-60min.

[0089] In the present invention, preferably, the amount of the film-forming resin is such that the content of the film-forming resin in the composite anti-seepage coating is 70-95% by weight; more preferably, the amount of the film-forming resin is such that the content of the film-forming resin in the composite anti-seepage coating is 80-90% by weight, for example, 70% by weight, 75% by weight and 85% by weight.

[0090] According to the present invention, preferably, the film-forming resin is selected from one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, novolac epoxy resin, polyurea resin, polyurethane resin, silicone resin and fluorocarbon resin; more preferably, the film-forming resin is novolac epoxy resin.

[0091] According to the present invention, preferably, based on the composite anti-seepage coating, the content of the redispersed graphene oxide-nano-titanium dioxide composite powder is 0.1-5 wt %; more preferably, the content of the redispersed graphene oxide-nano-titanium dioxide composite powder is 0.2-3 wt %.

[0092] According to the present invention, when the redispersible graphene oxide-nano titanium dioxide composite powder is ground with a film-forming resin, a step of adding a pigment is also included. The pigment can be any existing pigment that can be used in coatings. Preferably, the pigment is aniline black and / or yellow iron oxide. According to the present invention, preferably, the content of the pigment in the composite anti-seepage coating is 0.5-2% by weight; more preferably, the content of the pigment in the composite anti-seepage coating is 1-1.5% by weight.

[0093] According to the present invention, when the redispersible graphene oxide-nano titanium dioxide composite powder is mixed with another part of the film-forming resin, the step of adding an auxiliary agent is also included. The auxiliary agent can be various functional auxiliary agents that can be used in existing coatings. Preferably, the auxiliary agent is one or more of a wetting and dispersing agent, a leveling agent, an anti-settling agent, a defoaming agent, a matting agent and a thickener. The amount of the auxiliary agent can be selected according to the conventional amount in the art, and those skilled in the art can select it according to actual needs.

[0094] Preferably, the amount of the wetting and dispersing agent is such that the content of the wetting and dispersing agent in the composite anti-seepage coating is 1-5% by weight, more preferably 3-4% by weight.

[0095] Preferably, the amount of the leveling agent is such that the content of the leveling agent in the composite anti-seepage coating is 1-2% by weight, more preferably 1.4-1.6% by weight.

[0096] Preferably, the amount of the anti-settling agent is such that the content of the anti-settling agent in the composite anti-seepage coating is 1-7% by weight, more preferably 3-4% by weight.

[0097] Preferably, the defoaming agent is used in an amount such that the content of the defoaming agent in the composite anti-seepage coating is 1-4% by weight, more preferably 2-3% by weight.

[0098] Preferably, the amount of the matting agent is such that the content of the matting agent in the composite anti-seepage coating is 1-6% by weight, more preferably 1.5-3% by weight.

[0099] Preferably, the amount of the thickener used is such that the content of the thickener in the composite anti-seepage coating is 1-3% by weight, more preferably 1.5-2% by weight.

[0100] Preferably, the wetting and dispersing agent is polyester polyamide and / or polymethylaralkylsiloxane.

[0101] Preferably, the leveling agent is a polyether siloxane copolymer.

[0102] Preferably, the anti-settling agent is one or more of fumed silica, thixotropic resin and organic modified bentonite.

[0103] Preferably, the defoaming agent is polyether-modified silicon and / or polyether.

[0104] Preferably, the matting agent is diatomaceous earth and / or silicon dioxide.

[0105] Preferably, the thickener is polyethylene glycol and / or magnesium aluminum silicate.

[0106] According to the present invention, the composite anti-seepage coating is particularly suitable for oil storage tanks.

[0107] According to a second aspect of the present invention, a composite anti-seepage coating prepared by the preparation method of the composite anti-seepage coating of the present invention is provided.

[0108] According to the third aspect of the present invention, the composite anti-seepage coating prepared by the method for preparing the composite anti-seepage coating of the present invention is used in the internal anti-seepage of oil storage.

[0109] The present invention will be described in detail below by way of examples, but the present invention is not limited to the following examples.

[0110] Example 1

[0111] 1) Preparation of graphene oxide-nano-titanium dioxide composites

[0112] 1 part by weight of graphene oxide (purchased from Qingdao Laixi Colloidal Graphite Products Co., Ltd., particle size 30-38 μm) was mixed with 12 parts by weight of N'N-dimethylformamide (purchased from Beijing Chemical Industry Group Co., Ltd., analytical grade) and ultrasonically dispersed (dispersion power was 500 W, dispersion temperature was 25° C., and dispersion time was 1 h). 10 parts by weight of 3-aminopropyltriethoxysilane (purchased from Beijing Bailingwei Technology Co., Ltd.) was added to the solution, and nitrogen was continuously bubbled into the solution at room temperature (25° C.), and after maintaining for 0.5 h, the solution was heated to 100° C., stirred for 8 h for the first drying, and then washed 5 times with anhydrous ethanol (purchased from Shanghai Sigma Aldrich Trading Co., Ltd., analytical grade), and then first dried (drying temperature was 90° C., and drying time was 6 h) to obtain a first solid product. The first solid product was dissolved in N'N-dimethylformamide to obtain a solution containing the first solid product (the content of the first solid product was 8% by weight), the solution containing the first solid product was mixed with a 3% by weight nano titanium dioxide solution (purchased from Nanjing Reagent, analytically pure), acetic acid was added to adjust the pH value of the solution to 4, and then heated to 90°C, stirred for 8 hours, and then dried for a second time, wherein the weight ratio of nano titanium dioxide to graphene oxide was 1:2, and then washed with anhydrous ethanol for 5 times, and then dried for a second time at 60°C for 24 hours to obtain graphene oxide-nano titanium dioxide composite material A1;

[0113] 2) Preparation of redispersible graphene oxide-nano-titanium dioxide composite powder

[0114] The obtained graphene oxide-nano titanium dioxide composite material A1 was mixed with a polyaniline oligomer with an average molecular weight of 7500 (purchased from Hubei Watson Chemical Technology Co., Ltd.) for ultrasonic dispersion, wherein the weight ratio of graphene oxide to polyaniline oligomer was 1:30. After ultrasonic dispersion, the filtrate was filtered after standing at 25°C for 1 hour, and the filtrate was ultrasonically dispersed again and centrifuged, and the upper layer of the centrifuged liquid was taken to obtain a uniformly dispersed graphene oxide-nano titanium dioxide composite material dispersion. Among them, the conditions for ultrasonic dispersion are: power of 300W, temperature of 25°C, and time of 2h. The conditions for centrifugal separation are: speed of 12000r / min, temperature of 25°C, and time of 1.5h; the graphene oxide-nano titanium dioxide composite material dispersion was dried for a third time at 80°C for 10h to remove the solvent, and a redispersible graphene oxide-nano titanium dioxide composite powder B1 was obtained.

[0115] 3) Preparation of composite anti-seepage coating

[0116] Redispersible graphene oxide-nano titanium dioxide composite powder B1, pigment (aniline black, purchased from DuPont, USA) and part of film-forming resin (phenolic epoxy resin, 12% by weight of the total amount of film-forming resin, purchased from Nan Ya Plastic Industry Co., Ltd.) were mixed and ground at 20°C for 1 hour to obtain a color paste product. Another part of the film-forming resin and additives were added to the ground color paste product, and stirred and mixed in a stirrer for 30 minutes (temperature was 20°C) to obtain an anti-seepage coating S1. In addition, the amount of each component is shown in Table 1.

[0117] Example 2

[0118] 1) Preparation of graphene oxide-nano-titanium dioxide composites

[0119] 1 part by weight of graphene oxide (purchased from Ningbo Gaoxin Technology Co., Ltd., with a particle size of 32-40 μm) was mixed with 10 parts by weight of N'N-dimethylformamide (purchased from Beijing Chemical Industry Group Co., Ltd., analytical grade), and ultrasonically dispersed (the dispersion power was 400 W, the dispersion temperature was 25° C., and the dispersion time was 2 h). 5 parts by weight of 3-aminopropyltriethoxysilane (purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) was added to the solution, and nitrogen was continuously bubbled into the solution at room temperature (25° C.), and after maintaining for 1 h, the solution was heated to 100° C. and stirred for 10 h for the first drying, and then washed 5 times with anhydrous ethanol (purchased from Beijing Chemical Industry Group Co., Ltd., analytical grade), and then first dried (the drying temperature was 110° C. and the drying time was 8 h) to obtain a first solid product. The first solid product was dissolved in N'N-dimethylformamide to obtain a solution containing the first solid product (the content of the first solid product was 10% by weight), the solution containing the first solid product was mixed with a 2% by weight nano titanium dioxide solution (purchased from Nanjing Reagent, analytically pure), acetic acid was added to adjust the pH value of the solution to 4.5, and then heated to 90°C, stirred for 9 hours, and then dried for a second time, wherein the weight ratio of nano titanium dioxide to graphene oxide was 1:2.5, and then washed with anhydrous ethanol 4 times, and then dried for a second time at 50°C for 36 hours to obtain graphene oxide-nano titanium dioxide composite material A2;

[0120] 2) Preparation of redispersible graphene oxide-nano-titanium dioxide composite powder

[0121] The obtained graphene oxide-nano titanium dioxide composite material A2 was mixed with polyaniline oligomer with an average molecular weight of 7000 (purchased from Hubei Watson Chemical Technology Co., Ltd.) for ultrasonic dispersion, wherein the weight ratio of graphene oxide to polyaniline oligomer was 1:35. After ultrasonic dispersion, the mixture was allowed to stand at 25°C for 1 hour and then filtered to obtain a filtrate, and the filtrate was ultrasonically dispersed again and centrifuged, and the upper layer of the centrifuged liquid was taken to obtain a uniformly dispersed graphene oxide-nano titanium dioxide composite material dispersion, wherein the conditions for ultrasonic dispersion were: power of 400W, temperature of 25°C, time of 1.5h, and the conditions for centrifugal separation were: speed of 11000r / min, temperature of 25°C, time of 1.5h; the graphene oxide-nano titanium dioxide composite material dispersion was dried for a third time at 70°C for 15h to remove the solvent, and a redispersible graphene oxide-nano titanium dioxide composite powder B2 was obtained.

[0122] 3) Preparation of composite anti-seepage coating

[0123] Redispersible graphene oxide-nano titanium dioxide composite powder B2, pigment (aniline black, purchased from DuPont, USA) and part of film-forming resin (phenolic epoxy resin, 10% by weight of the total amount of film-forming resin, purchased from Chongqing Yonghua Chemical Group Co., Ltd.) were mixed and ground at 25°C for 1.5h to obtain a color paste product. The remaining film-forming resin and additives were added to the ground color paste product, and stirred in a stirrer for 60min (temperature was 25°C) to obtain an anti-seepage coating S2. In addition, the amount of each component is shown in Table 1.

[0124] Example 3

[0125] 1) Preparation of graphene oxide-nano-titanium dioxide composites

[0126] 1 part by weight of graphene oxide (purchased from Qingdao Laixi Colloidal Graphite Products Co., Ltd., with a particle size of 30-38 μm) was mixed with 15 parts by weight of N'N-dimethylformamide (purchased from Sinopharm Chemical Reagent Co., Ltd., analytical grade) and ultrasonically dispersed (the dispersion power was 500 W, the dispersion temperature was 30°C, and the dispersion time was 1 h). After uniform dispersion, 6 parts by weight of 3-aminopropyltriethoxysilane (purchased from Sinopharm Chemical Reagent Co., Ltd.) were added to the solution, and nitrogen was continuously bubbled into the solution at 30°C. After maintaining for 1 h, the solution was heated to 100°C and stirred for 9 h for the first drying. Then, it was rinsed 4 times with anhydrous ethanol (purchased from Shanghai Sigma-Aldrich Trading Co., Ltd.), and then the first drying was performed (the drying temperature was 100°C and the drying time was 6 h) to obtain a first solid product. The first solid product was dissolved in N'N-dimethylformamide to obtain a solution containing the first solid product (the content of the first solid product was 9 weight %), the solution containing the first solid product was mixed with a 2 weight % nano titanium dioxide solution (purchased from Nanjing Reagent, analytical grade), and citric acid was added to adjust the pH value of the solution to 5, and then heated to 90° C., stirred for 10 hours, and then dried for a second time, wherein the weight ratio of nano titanium dioxide to graphene oxide was 1:2, and then washed with anhydrous ethanol for 5 times, and then dried for a second time at 60° C. for 48 hours to obtain graphene oxide-nano titanium dioxide composite material A3;

[0127] 2) Preparation of redispersible graphene oxide-nano-titanium dioxide composite powder

[0128] The obtained graphene oxide-nano titanium dioxide composite material A3 was mixed with polyaniline oligomer with an average molecular weight of 8000 (purchased from Shanghai Haohong Biomedical Technology Co., Ltd.) for ultrasonic dispersion, wherein the weight ratio of graphene oxide to polyaniline oligomer was 1:32. After ultrasonic dispersion, the filtrate was filtered after standing at 30°C for 2h, and the filtrate was ultrasonically dispersed again and centrifuged, and the upper layer of the centrifuged liquid was taken to obtain a uniformly dispersed graphene oxide-nano titanium dioxide composite material dispersion. Among them, the conditions for ultrasonic dispersion were: power of 350W, temperature of 27°C, time of 3h, and the conditions for centrifugal separation were: speed of 10000r / min, temperature of 25°C, and time of 2h. After the graphene oxide-nano titanium dioxide composite material dispersion was dried for the third time at 90°C for 20h to remove the solvent, a redispersible graphene oxide-nano titanium dioxide composite powder B3 was obtained.

[0129] 3) Preparation of composite anti-seepage coating

[0130] The redispersible graphene oxide-nano titanium dioxide composite powder B3, pigment (iron oxide yellow, purchased from Tianjin Jifa Pigment Co., Ltd.) and part of the film-forming resin (phenolic epoxy resin, 11% by weight of the total amount of film-forming resin, purchased from Nantong Xingchen Synthetic Materials Co., Ltd.) were mixed and ground at 25° C. for 2 h to obtain a color paste product. The remaining film-forming resin and additives were added to the ground color paste product, and stirred in a stirrer for 45 min (temperature was 25° C.) to obtain an anti-seepage coating S3. In addition, the amount of each component is shown in Table 1.

[0131] Example 4

[0132] 1) Preparation of graphene oxide-nano-titanium dioxide composites

[0133] 1 part by weight of graphene oxide (purchased from Changzhou Sixth Element Material Technology Co., Ltd., with a particle size of 35-40 μm) was mixed with 14 parts by weight of N'N-dimethylformamide (purchased from Shanghai McLean Biochemical Technology Co., Ltd., analytical grade) and ultrasonically dispersed (the dispersion power was 400 W, the dispersion temperature was 25° C., and the dispersion time was 1.5 h). After uniform dispersion, 12 parts by weight of 3-aminopropyltriethoxysilane (purchased from Sinopharm Chemical Reagent Co., Ltd.) was added to the solution, and nitrogen was continuously bubbled into the solution at room temperature (25° C.) for 0.5 h. The solution was then heated to 100° C. and stirred for 10 h for a first drying. The solution was then rinsed 5 times with anhydrous ethanol (purchased from Shanghai McLean Biochemical Technology Co., Ltd., analytical grade) and then dried for a first time (the drying temperature was 90° C. and the drying time was 7 h) to obtain a first solid product. The first solid product was dissolved in N'N-dimethylformamide to obtain a solution containing the first solid product (the content of the first solid product was 10% by weight), the solution containing the first solid product was mixed with a 5% by weight nano titanium dioxide solution (purchased from Nanjing Reagent, analytically pure), acetic acid was added to adjust the pH value of the solution to 4.5, and then heated to 90°C, stirred for 10 hours, and then dried for a second time, wherein the weight ratio of nano titanium dioxide to graphene oxide was 1:1.5, and then washed with anhydrous ethanol for 5 times, and then dried for a second time at 70°C for 24 hours to obtain graphene oxide-nano titanium dioxide composite material A4;

[0134] 2) Preparation of redispersible graphene oxide-nano-titanium dioxide composite powder

[0135] The obtained graphene oxide-nano titanium dioxide composite material A4 was mixed with polyaniline oligomer with an average molecular weight of 7000 (purchased from Hubei Watson Chemical Technology Co., Ltd.) for ultrasonic dispersion, wherein the weight ratio of graphene oxide to polyaniline oligomer was 1:35. After ultrasonic dispersion, the filtrate was filtered after standing at 25°C for 2.5 hours, and the filtrate was ultrasonically dispersed again and centrifuged, and the upper layer of the centrifuged liquid was taken to obtain a uniformly dispersed graphene oxide-nano titanium dioxide composite material dispersion. Among them, the conditions for ultrasonic dispersion were: power of 400W, temperature of 25°C, time of 1.5h, and the conditions for centrifugal separation were: speed of 13000r / min, temperature of 25°C, time of 1.5h; the graphene oxide-nano titanium dioxide composite material dispersion was dried for the third time at 75°C for 12h to remove the solvent, and a redispersible graphene oxide-nano titanium dioxide composite powder B4 was obtained.

[0136] 3) Preparation of composite anti-seepage coating

[0137] Redispersible graphene oxide-nano titanium dioxide composite powder B4, pigment (iron oxide yellow, purchased from Tianjin Jifa Pigment Co., Ltd.) and part of film-forming resin (phenolic epoxy resin, 15% by weight of the total amount of film-forming resin, purchased from BASF AG, Germany) were mixed and ground at 25°C for 2h to obtain a color paste product. The remaining film-forming resin and additives were added to the ground color paste product, and stirred in a stirrer for 30min (temperature was 25°C) to obtain an anti-seepage coating S4. In addition, the amount of each component is shown in Table 1.

[0138] Example 5

[0139] 1) Preparation of graphene oxide-nano-titanium dioxide composites

[0140] 1 part by weight of graphene oxide (purchased from Changzhou Sixth Element Material Technology Co., Ltd., with a particle size of 35-40 μm) was mixed with 16 parts by weight of N'N-dimethylformamide (purchased from Shanghai McLean Biochemical Technology Co., Ltd., analytical grade) and ultrasonically dispersed (the dispersion power was 300 W, the dispersion temperature was 25°C, and the dispersion time was 3 h). After uniform dispersion, 18 parts by weight of 3-aminopropyltriethoxysilane (purchased from Sinopharm Chemical Reagent Co., Ltd.) was added to the solution, and nitrogen was continuously bubbled into the solution at room temperature (25°C). After maintaining for 1.5 h, the solution was heated to 90°C and stirred for 7 h for the first drying. Then, it was rinsed 5 times with anhydrous ethanol (purchased from Shanghai McLean Biochemical Technology Co., Ltd., analytical grade), and then the first drying was performed (the drying temperature was 90°C and the drying time was 7 h) to obtain a first solid product. The first solid product was dissolved in N'N-dimethylformamide to obtain a solution containing the first solid product (the content of the first solid product was 12% by weight), the solution containing the first solid product was mixed with a 5% by weight nano titanium dioxide solution (purchased from Nanjing Reagent, analytically pure), acetic acid was added to adjust the pH value of the solution to 5.5, and then heated to 80°C, stirred for 10 hours, and then dried for a second time, wherein the weight ratio of nano titanium dioxide to graphene oxide was 1:3, and then washed with anhydrous ethanol for 5 times, and then dried for a second time at 70°C for 18 hours to obtain graphene oxide-nano titanium dioxide composite material A5;

[0141] 2) Preparation of redispersible graphene oxide-nano-titanium dioxide composite powder

[0142] The obtained graphene oxide-nano titanium dioxide composite material A4 was mixed with polyaniline oligomer with an average molecular weight of 8500 (purchased from Shanghai Haohong Biomedical Technology Co., Ltd.) for ultrasonic dispersion, wherein the weight ratio of graphene oxide to polyaniline oligomer was 1:45. After ultrasonic dispersion, the filtrate was filtered after standing at 25°C for 2 hours, and the filtrate was ultrasonically dispersed again and centrifuged, and the upper liquid of the centrifuged separation was taken to obtain a uniformly dispersed graphene oxide-nano titanium dioxide composite material dispersion. Among them, the conditions for ultrasonic dispersion were: power of 500W, temperature of 25°C, time of 1.5h, and the conditions for centrifugal separation were: speed of 13000r / min, temperature of 25°C, and time of 2h; the graphene oxide-nano titanium dioxide composite material dispersion was dried for the third time at 60°C for 12h to remove the solvent, and a redispersible graphene oxide-nano titanium dioxide composite powder B5 was obtained.

[0143] 3) Preparation of composite anti-seepage coating

[0144] Redispersible graphene oxide-nano titanium dioxide composite powder B5, pigment (iron oxide yellow, purchased from Tianjin Jifa Pigment Co., Ltd.) and part of film-forming resin (phenolic epoxy resin, 18% by weight of the total amount of film-forming resin, purchased from BASF AG, Germany) were mixed and ground at 25°C for 2h to obtain a color paste product. The remaining film-forming resin and additives were added to the ground color paste product, and stirred in a stirrer for 40min (temperature was 25°C) to obtain an anti-seepage coating S5. In addition, the amount of each component is shown in Table 1.

[0145] Table 1

[0146]

[0147] In Table 1, the content of each component is based on the total weight of the anti-seepage coating as 100 weight %. The "composite powder" uses the redispersible graphene oxide-nano titanium dioxide composite powder obtained in each embodiment; the wetting and dispersing agent is polyester polyamide (purchased from BASF AG, Germany); the leveling agent is polyether siloxane copolymer (purchased from Hubei Longsheng Sihai New Materials Co., Ltd.); the anti-settling agent is fumed silica (purchased from Wacker, Germany); the defoaming agent is polyether modified silicon (purchased from Yantai Hengxin Chemical Technology Co., Ltd.); the matting agent is diatomaceous earth (purchased from Hebei Hengyue Mineral Products Co., Ltd.); the thickener is polyethylene glycol (purchased from BASF AG, Germany).

[0148] Comparative Example 1

[0149] The method of Example 1 is followed, except that step 1) is not included, and graphene is directly used instead of the graphene oxide-nano-titanium dioxide composite material A1, and the anti-seepage coating D1 is obtained in the same manner.

[0150] Comparative Example 2

[0151] The method of Example 1 is followed, except that step 1) is not included, and graphene oxide is directly used instead of the graphene oxide-nano-titanium dioxide composite material A1, and the anti-seepage coating D2 is obtained in the same manner.

[0152] Comparative Example 3

[0153] The method of Example 1 is followed, except that step 2) is not included, and the redispersible graphene oxide-nano-titanium dioxide composite material A1 is directly used to replace the redispersible graphene oxide-nano-titanium dioxide composite powder B1, and the anti-seepage coating D3 is obtained in the same manner.

[0154] Test Example 1

[0155] The obtained anti-seepage coatings S1, S2, S3, S4, S5, D1, D2, and D3 were coated on polytetrafluoroethylene samples using an automatic coating machine (TBJ-A1-DJ4, Shandong Zhongyi Instrument Co., Ltd.), and the film thickness was controlled to be 20 μm. After being completely cured and cured at room temperature for 5 days, the water vapor transmission rate of the anti-seepage coating was tested according to the cup weight method described in standard ASTM E96 / E96M. The results are shown in the figure. Figure 1 shown.

[0156] Test Example 2

[0157] The obtained anti-seepage coatings S1, S2, S3, S4, S5, D1, D2, and D3 were coated on copper foil with a thickness of 100 μm after curing. After curing, they were used as samples for corrosion resistance testing using the method for determining the neutral salt spray resistance of paints and varnishes in GB / T1771. The results are shown in Table 2.

[0158] Table 2

[0159] type Salt spray resistance time / h S1 5800 S2 5400 S3 6000 S4 5800 S5 4800 D1 2000 D2 2600 D3 4000

[0160] Test Example 3

[0161] The obtained anti-seepage coatings S1, S2, S3, S4, S5, D1, D2, and D3 were cast in a mold of 8×1.5×0.3 cm. After being completely cured and cured at room temperature for 5 days, the cast materials were placed in crude oil (sampled from the crude oil reservoir of Sinopec Shengli Oilfield) and immersed at room temperature of 25°C for 30 days. The surface morphology was observed as follows: Figure 2 The test results are listed in Table 3.

[0162] Table 3

[0163] type Material status after immersion S1 No abnormality S2 No abnormality S3 No abnormality S4 No abnormality S5 No abnormality D1 Breakage, blistering D2 Foaming D3 Foaming

[0164] Test Example 4

[0165] The obtained anti-seepage coatings S1, S2, S3, S4, S5, D1, D2, and D3 were cast in a mold of 8×1.5×0.3 cm. After being completely cured and cured at room temperature for 5 days, the casting material was placed in the sediment water at the bottom of the crude oil tank (sampled from the crude oil reservoir of Sinopec Shengli Oilfield) and immersed at room temperature of 25°C for 30 days. The change of its Shore hardness over time was tested according to standard GB / T2411-2008. Figure 3 shown.

[0166] comprehensive Figure 1 ,Table 2, Figure 2 , Table 3 and Figure 3 The test results show that the redispersible graphene oxide-nano titanium dioxide composite powder filler used in the titanium dioxide modified graphene oxide composite anti-seepage coating of the present invention has better water vapor barrier performance, salt spray resistance, resistance to crude oil and water deposited at the bottom of crude oil tanks than graphene, graphene oxide and graphene oxide-nano titanium dioxide composite material filler without dispersion polyaniline oligomer. This is because the coupling modification of graphene oxide with nano-titanium dioxide particles can enhance the dispersibility of graphene oxide, and can make up for the structural defects of graphene oxide by blocking micropores. In addition, the use of polyaniline oligomers for filler-assisted dispersion can further improve the dispersibility of the work filler in the resin matrix, thereby extending the penetration and diffusion path of the corrosive medium and producing a better medium shielding effect.

[0167] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a composite anti-seepage coating, characterized in that: The Method The following steps are included: 1) in the presence of a solvent, allowing graphene oxide and a silane coupling agent to undergo a first contact reaction, and subjecting the first contact reaction product to a first drying to obtain a first solid product; 2) Under acidic conditions, subjecting the solution containing the first solid product to a second contact reaction with a titanium dioxide solution, and subjecting the second contact reaction product to a second drying to obtain a second solid product; 3) using polyaniline oligomer as a dispersant to disperse the second solid product obtained in step 2), and thirdly drying to obtain a redispersible graphene oxide-nano-titanium dioxide composite powder; 4) Mixing the redispersible graphene oxide-nano titanium dioxide composite powder obtained in step 3) with a film-forming resin.

2. The method according to claim 1, wherein: In step 1), the weight ratio of the graphene oxide to the solvent is 1:8-20, preferably 1:10-15; Preferably, the weight ratio of the graphene oxide to the silane coupling agent is 1:3-18, preferably 1:5-15.

3. The method according to claim 1, wherein: In step 1), the first contact reaction is carried out under an inert atmosphere; Preferably, the first contact reaction conditions include: temperature of 10-35°C, reaction time of 0.2-2h; Preferably, the first contact reaction conditions include: temperature of 25-30°C, reaction time of 0.5-1h; Preferably, the first drying conditions include: temperature of 70-150°C and time of 4-15h; Preferably, the first drying conditions are: temperature of 90-110° C. and time of 6-10 h.

4. The method according to claim 1, wherein: In step 1), the solvent is selected from one or more of N'N-dimethylformamide, N'N-dimethylacetamide and N'N-dimethylpropionamide, preferably N'N-dimethylformamide; Preferably, the silane coupling agent includes one or more selected from 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, preferably 3-aminopropyltriethoxysilane.

5. The method according to claim 1, wherein: The method further comprises: before the first drying, performing a first drying and washing step on the first contact reaction product.

6. The method according to claim 1, wherein: In step 2), the solvent used in the solution containing the first solid product is selected from one or more of N'N-dimethylformamide, N'N-dimethylacetamide and N'N-dimethylpropionamide; Preferably, the content of the first solid product in the solution containing the first solid product is 5-10% by weight; Preferably, the acidic condition is a pH value between 3.5-5.5, preferably a pH value of 4-5; Preferably, the acidic conditions are adjusted by adding acetic acid.

7. The method according to claim 1, wherein: In step 2), the concentration of the nano titanium dioxide solution is 0.5-7% by weight, preferably 2-5% by weight; Preferably, the weight ratio of the nano titanium dioxide to the graphene oxide is 1:1-4, preferably 1:1.5-2.

5.

8. The method according to claim 1, wherein: In step 2), the second contact reaction conditions include: temperature of 60-90°C and time of 5-12h; Preferably, the second contact reaction conditions include: temperature of 80°C and time of 6-10h; Preferably, the second drying conditions include: temperature of 45-100°C and time of 18-64h; Preferably, the second drying conditions include: temperature of 50-90° C. and time of 24-48 hours.

9. The method according to claim 1, wherein: The method further comprises: before the second drying, performing a second drying and washing step on the second contact reaction product.

10. The method according to claim 1, wherein: In step 3), the average molecular weight of the polyaniline oligomer is 6000-10000, preferably 7000-8000; Preferably, the weight ratio of the graphene oxide to the polyaniline oligomer is 1:20-60, preferably 1:30-40.

11. The method according to claim 1, wherein: In step 3), the dispersion is ultrasonic dispersion; Preferably, the conditions for ultrasonic dispersion include: ultrasonic power of 100-500W, ultrasonic time of 0.2-5h; Preferably, the conditions for ultrasonic dispersion include: ultrasonic power of 200-400W, and ultrasonic time of 0.5-3h.

12. The method according to claim 1, wherein: In step 3), the conditions of the third drying include: temperature of 50-95°C and time of 6-30h; Preferably, the conditions for the third drying include: a temperature of 70-90° C. and a time of 10-20 hours.

13. The method according to claim 1, wherein: In step 4), the redispersible graphene oxide-nano titanium dioxide composite powder obtained in step 3) and a portion of the film-forming resin are ground and then mixed with another portion of the film-forming resin; Preferably, the redispersible graphene oxide-nano titanium dioxide composite powder and 5-20 weight % of the total amount of the film-forming resin are ground; Preferably, the redispersible graphene oxide-nano titanium dioxide composite powder is ground with 10-15 weight % of the total amount of the film-forming resin; Preferably, based on the composite anti-seepage coating, the content of the redispersed graphene oxide-nano-titanium dioxide composite powder is 0.1-5% by weight, preferably 0.2-3% by weight.

14. The method according to claim 1, wherein: The method further comprises: in step 4), a step of adding an auxiliary agent; Preferably, the auxiliary agent is a pigment; Preferably, based on the composite anti-seepage coating, the content of the auxiliary agent is 0.5-2% by weight.

15. The method according to claim 1, wherein: In step 4), the film-forming resin is selected from one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, novolac epoxy resin, polyurea resin, polyurethane resin, silicone resin and carbon fiber resin, preferably novolac epoxy resin.

16. The composite anti-seepage coating prepared by the preparation method of the composite anti-seepage coating according to any one of claims 1 to 15.

17. Use of the composite anti-seepage coating prepared by the preparation method of the composite anti-seepage coating according to any one of claims 1 to 15 or the composite anti-seepage coating according to claim 16 in anti-seepage inside oil storage.

Citation Information

Patent Citations

  • Graphene composite coating, graphene composite paint and preparation method thereof

    CN105802452A

  • Anticorrosive and conductive coating and preparation method thereof

    CN106010091A

  • Composite anticorrosive material containing modified graphene oxide and preparation method thereof

    CN114958151A

  • Preparation method of graphene / epoxy resin anticorrosive coating

    CN110183939A

  • Amphiphilic graphene oxide and preparation method thereof and application in waterborne coating thereof

    CN110240814A